Integration of ISO/IEC 17025:2017 and ISO 35001:2019 into the Quality Management and Biosafety System of Clinical Microbiology Laboratories - Ihsan Hakim Haviana; Dwintha Lestari; Alfi Fitriyani; Evan Haviana (Indonesian Health Issue, 2026)
Background: Clinical microbiology laboratories play a strategic role in healthcare systems, particularly in infectious disease diagnosis, infection control, and outbreak surveillance. However, their operations pose high biological risks, requiring management systems that ensure both test quality and biosafety. Purpose: This study aims to analyze the integration of ISO/IEC 17025:2017, which focuses on testing and calibration laboratory competence, and ISO 35001:2019, which governs biorisk management, as a model for strengthening quality and safety systems in clinical microbiology laboratories. Methods: A Systematic Literature Review (SLR) was conducted following PRISMA guidelines, covering 107 articles from Google Scholar, Scopus, PubMed, and Semantic Scholar. After screening, 17 relevant studies were thematically and bibliometrically analyzed. Results: The results revealed that integrating ISO/IEC 17025 and ISO 35001 improved test validity, increased audit efficiency by 30%, and reduced laboratory incidents by 40%. Major challenges in developing countries include limited human resources, fragmented regulations, and low levels of digitalization. Conclusion: The study concludes that integrating these standards establishes a risk-based management system that is adaptive and oriented toward continuous improvement. Cross-sectoral strategies based on the One Health Biosafety Framework are recommended to strengthen national policies and develop resilient, safe, and internationally competitive clinical laboratory systems.